Особливості використання стандартів ieee 802.11 для реалізації БСМ - Красніков, А. О. (ХНУРЕ, 2022)
The advantages of wireless sensor networks in comparison with conventional computer networks are shown. The features of the BSM are analyzed from the point of view of the ability of self-healing and self-organization. The possibility of using Wi-Fi technology for the implementation of BMS is considered. It is shown that for organizing hierarchical wireless «Ad-hoc» networks with mobile and static nodes, the IEEE 802.11s standard can be used as a promising one. The possibilities and advantages of this standard in comparison with earlier releases are substantiated.